The moral economy : poverty, credit, and trust in early modern Europe - Fontaine, Laurence (New York: Cambridge Univ. Press, 2014)
The moral economy analyzes the nexus of poverty, credit, and trust in early modern Europe.
Includes bibliographical references and index.
aia 24/10/17
Loans
Keywords: Poverty; Credit; Usury; Loans; Trust; Econopmic history; Europe